2012
DOI: 10.1002/sec.528
|View full text |Cite
|
Sign up to set email alerts
|

What you see predicts what you get—lightweight agent‐based malware detection

Abstract: Because of the always connected nature of mobile devices, as well as the unique interfaces they expose, such as short message service (SMS), multimedia messaging service (MMS), and Bluetooth, classes of mobile malware tend to propagate using means unseen in the desktop world. In this paper, we propose a lightweight malware detection system on mobile devices to detect, analyze, and predict malware propagating via SMS and MMS messages. We deploy agents in the form of hidden contacts on the device to capture mess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Power law, which is also known as the 80:20 rule or Pareto principle, exponential, and log‐normal distributions are addressed in the literature that tends to search for a specific statistical distribution to discover the characteristics of many natural and unnatural phenomena. The example phenomena reflecting these distributions are compiled and categorized from (Limpert et al, 2001; Milojević, 2010; Newman, 2004; White et al, 2008) or other resources with given references as follows: Natural phenomena fitting log‐normal : element concentration in the Earth's crust, latent periods (from infection to the first symptoms) of infectious disease [e.g., the incubation period of Coronavirus disease 2019 (COVID‐19), SARS (severe acute respiratory syndrome), and MERS (Middle East Respiratory Syndrome; Backer et al, 2020)], the abundance of bacteria on plants; Unnatural phenomena fitting log‐normal : number of letters per word, number of words per sentence, age of first marriage in Western; Natural phenomena fitting exponential : damage in nuclear power incidents and accidents before 1980 (Wheatley et al, 2017), moderate‐sized disasters (observed sea‐level variations, wind velocity, annual river floods) (Pisarenko & Rodkin, 2010), the arrival rate of cosmic ray alpha particles or Geiger counter tics (Tobias, 2012); Unnatural phenomena fitting exponential : time to failure patterns (also in natural phenomena) (Frank, 2009), modeling malware propagation delays (Wang & Murynets, 2013), frequency of Korean family names (power law in family names in the world), intervals between aircraft arrivals to major airports (Willemain et al, 2004), the inter‐arrival times of the 911 calls (Albert, 2011), the time between goals in World Cup football matches (Chu, 2003), the dispersion of U.S. incomes which was qualified as a kind of thermal equilibrium (Bartels, 2012); Natural phenomena fitting power law : island sizes, lake sizes, flood magnitudes, species body sizes, individual body sizes (White et al, 2008), basic community structure descriptors (number of species, links, and links per species) with the area (Galiana et al, 2022); and Unnatural phenomena fitting power law : author productivity, citations received by papers, scattering of scientific literature (Milojević, 2010). Component sizes in component‐based software development (Sharma & Pendharkar, 2022).…”
Section: Fitting Binary Feature Frequencies Into a Statistical Distri...mentioning
confidence: 99%
“…Power law, which is also known as the 80:20 rule or Pareto principle, exponential, and log‐normal distributions are addressed in the literature that tends to search for a specific statistical distribution to discover the characteristics of many natural and unnatural phenomena. The example phenomena reflecting these distributions are compiled and categorized from (Limpert et al, 2001; Milojević, 2010; Newman, 2004; White et al, 2008) or other resources with given references as follows: Natural phenomena fitting log‐normal : element concentration in the Earth's crust, latent periods (from infection to the first symptoms) of infectious disease [e.g., the incubation period of Coronavirus disease 2019 (COVID‐19), SARS (severe acute respiratory syndrome), and MERS (Middle East Respiratory Syndrome; Backer et al, 2020)], the abundance of bacteria on plants; Unnatural phenomena fitting log‐normal : number of letters per word, number of words per sentence, age of first marriage in Western; Natural phenomena fitting exponential : damage in nuclear power incidents and accidents before 1980 (Wheatley et al, 2017), moderate‐sized disasters (observed sea‐level variations, wind velocity, annual river floods) (Pisarenko & Rodkin, 2010), the arrival rate of cosmic ray alpha particles or Geiger counter tics (Tobias, 2012); Unnatural phenomena fitting exponential : time to failure patterns (also in natural phenomena) (Frank, 2009), modeling malware propagation delays (Wang & Murynets, 2013), frequency of Korean family names (power law in family names in the world), intervals between aircraft arrivals to major airports (Willemain et al, 2004), the inter‐arrival times of the 911 calls (Albert, 2011), the time between goals in World Cup football matches (Chu, 2003), the dispersion of U.S. incomes which was qualified as a kind of thermal equilibrium (Bartels, 2012); Natural phenomena fitting power law : island sizes, lake sizes, flood magnitudes, species body sizes, individual body sizes (White et al, 2008), basic community structure descriptors (number of species, links, and links per species) with the area (Galiana et al, 2022); and Unnatural phenomena fitting power law : author productivity, citations received by papers, scattering of scientific literature (Milojević, 2010). Component sizes in component‐based software development (Sharma & Pendharkar, 2022).…”
Section: Fitting Binary Feature Frequencies Into a Statistical Distri...mentioning
confidence: 99%
“…A lightweight malware detection system for detecting, analysing and predicting malware propagating via SMS and MMS messages on mobile devices is proposed in [28]. It deploys agents in the form of hidden contacts on the device to capture messages sent from malicious applications.…”
Section: Related Workmentioning
confidence: 99%
“…Project Honey Pot [15] employed a web based honeypot network which uses software embedded in web sites to collect information about IPs harvesting e-mail addresses for spam, bulk mailing and fraud. Most recently on the mobile communications front, Collin [16] implemented HoneyDroid, a smartphone honeypot for the Android operating system to catch attacks originating from the Internet, mobile networks, as well as through malicious applications; while Wang [24] introduced fake contacts on mobile devices to quickly detect messaging-based malware propagation in cellular networks. Brian et al [8] proposed trap-based defense mechanisms and a deployment platform for addressing the problem of insiders attempting to exfiltrate and use sensitive information.…”
Section: Related Workmentioning
confidence: 99%